Resilience achieved via multiple compensating subsystems: The immediate impacts of COVID-19 control measures on the agri-food systems of Australia and New Zealand. (February 2021) - Snow, Val; Rodriguez, Daniel; Dynes, Robyn; Kaye-Blake, William; Mallawaarachchi, Thilak; Zydenbos, Sue; Cong, Lei; Obadovic, Irena; Agnew, Rob; Amery, Nicole; Bell, Lindsay; Benson, Cristy; et al.
Abstract: Context: Since COVID-19 (SARS-CoV-2) was first identified in the human population, it has had immediate and significant effects on peoples' health and the worldwide economy. In the absence of a vaccine, control of the virus involved limiting its spread through restrictions in the movement of people, goods and services. This has led to unprecedented impacts on labour availability, provision of goods and services, value chains, and markets. Objective: Against the backdrop of COVID-19 control measures, this article summarises quantitative and qualitative assessments of the impacts, adaptations, and opportunities to increase the resilience of the agricultural systems in Australia and New Zealand. Methods: Using both survey and interview methodologies, we describe the various agri-food systems and the impacts of the COVID-19 control measures across different industries, and discuss the results applying a resilience framework. Results: As essential services, all agricultural activities except for fibre production have been permitted to continue during quarantine periods but have been exposed to the major flow-on effects of movement control. We found that, to June 2020, the impacts of the COVID-19 control measures on the agri-food sectors in both Australia and New Zealand have been relatively small and that this has been due to the high levels of resilience in the agricultural systems and the people running them. Conclusions: We consider agri-food systems to be comprised of multiple subsystems with varying vulnerability to external influences. Agri-food systems were resilient to June 2020 at least, and that resilience was achieved via one or more subsystems that were able to compensate for the more vulnerable subsystems. We contrast the resilience of industries that have high plasticity (that can have a flow of material that can safely vary in time) to more rigid industries that are dependent on a steady flow of material with little or no storage. Ultimately both types of industries were resilient, but they achieved that resilience via compensating subsystems. High plasticity industries relied on their production and processing subsystem; rigid industries engaged their institutional subsystem to achieve the same end. The social and cultural subsystem was important across all industries. Significance: It is not yet clear if the current resilience mechanisms can persist under the continued onslaught of the virus. We indicate the need to capture longer term effects and analysis during the more sustained effects of the virus and through a recovery period. We anticipate a follow-up study in 2022. Graphical abstract: Unlabelled Image Highlights: Restrictions on physical gatherings to control COVID-19 has impacted agri-food systems via labour, goods and services, value chains and markets We sought to understand the impacts by surveying and interviewing individuals across many industries and sectors in Australia and New Zealand To June 2020, the industries have proved resilient but that resilience was achieved via multiple compensating subsystems Industries with high plasticity used a production subsystem for resilience; low plasticity industries engaged an institutional subsystem for the same end A follow-up study is needed to understand if the existing resilience mechanisms will withstand the continued onslaught of COVID-19